Evaluating Organizational Hypocrisy within Universities as Toxic Leadership Behavior. (4th July 2021) - Yaghi, Abdulfattah; Yaghi, Majed
Abstract : As academic managers, college deans, associate deans, assistant deans, department chairs, and program coordinators play pivotal leadership roles within universities. It is, therefore, crucial to understand their organizational behavior. Without ascribing causal values to conduct, this study hypothesizes that academic managers repeatedly practice workplace hypocrisy. To test this postulation, the study seeks to identify the characteristics of perceived hypocrisy before exploring the possible similarities between hypocritical behavior and toxic leadership behavior. The data were obtained via open-ended questions answered by 175 academic managers and 517 professors working in 13 universities. The results of the analyses support the initial hypothesis: 81% of all respondents reported experiencing more than one hypocritical incident in the last year; 84% of the academic managers and 64% of the professors testified to being directly affected by first-hand hypocrisy. The responses revealed four groups of hypocritical characteristics; dishonesty, attacking others, disregard to institutional wellbeing, and disingenuous personality. Similarities between hypocritical and toxic characteristics were discussed followed by theoretical and practical implications of the findings.